The electrochemistry of a heme-containing enzyme, CYP199A2, adsorbed directly onto a pyrolytic graphite electrode - Fleming, B; Bell, S; Wong, L; Bond, A (2007)
The dc and Fourier transformed ac voltammetries of the cytochrome P450 enzyme, CYP199A2 from Rhodopseudomonas palustris, when directly adsorbed onto an unmodified pyrolytic graphite electrode, are consistent with a one-electron, quasi-reversible, charge transfer process. Analysis of data show that the formal reversible potential of surface-confined CYP199A2 measured in phosphate buffer solution (pH 7.0, 0.1 M NaCl) is -0.132 ± 0.002 V (vs. SHE) and that electrons can be rapidly transferred between the electrode and the enzyme (rate constant at the reversible potential, ks = 550 ± 50 s-1). Proton-coupled electron transfer, CO and O2 binding are evident, consistent with P450 heme involvement in the redox process. Binding of the protein to the electrode is rapid and strong, with significant Faradaic current being detected after less than 1 min of protein exposure to the electrode surface, and little decrease in the current magnitude observed over several hours. Interestingly, the heme domain of CYP102A1, another bacterial P450 enzyme, is not electrochemically active under the same conditions. Analysis derived from crystal structure data indicates that binding and electron transfer may be facilitated by the interaction between a patch of positively charged amino acid residues located on the surface of the protein, just above the proximal face of the heme, and negatively charged functional groups located along the exposed edge-planes of the pyrolytic graphite electrode. © 2007 Elsevier B.V. All rights reserved.